Increased contact system activation in MCI patients with impaired short-term memory - Singh, Pradeep K. (J Alzheimers Dis, 2020)
An activated plasma contact system is an abnormality observed in many Alzheimer’s disease (AD) patients. Since mild cognitive impairment (MCI) patients often develop AD, we analyzed the status of contact system activation in MCI patients. We found that kallikrein activity, high molecular weight kininogen cleavage, and bradykinin levels – measures of contact system activation – were significantly elevated in MCI patient plasma compared to plasma from age- and education-matched healthy individuals. Changes were more pronounced in MCI patients with impaired short-term recall memory, indicating the possible role of the contact system in early cognitive changes.